MONITORING OF THE EFFECTIVENESS OF ANTIPLATELET THERAPY IN CARDIOLOGY PRACTICE - N. F. Puchinian; N. V. Furman; L. I. Malinova; P. V. Dolotovskaya (Столичная издательская компания, 2017)
Monitoring of the effectiveness of drug therapy is one of the most debated issues in everyday clinical practice. The emergence of new drugs,  methods of analysis, standards, management protocols, and clinical guidelines increases the information load on practitioners and requires a significant investment of time and efforts for self-education. The purpose of the review is to help practitioners in summary form to obtain the necessary information on the issue of control of antiplatelet therapy. The review brings together data  from current  clinical recommendations on antiplatelet therapy in patients with ischemic heart disease, gives information of existing approaches to control of antiplatelet therapy specified in the guidelines and the consensuses of experts. It presents information on the most common modern methods of monitoring of the antiplatelet therapy effectiveness.